2016
DOI: 10.3758/s13423-016-1141-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous adaptation explains why people act faster when being imitated

Abstract: The human ability to perform joint actions is often attributed to high-level cognitive processes. For example, the finding that action leaders act faster when imitated by their partners has been interpreted as evidence for anticipation of the other’s actions (Pfister, Dignath, Hommel, & Kunde, 2013). In two experiments, we showed that a low-level mechanism can account for this finding. Action leaders were faster when imitated than when counterimitated, but only if they could observe their partner’s actions (Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 45 publications
6
12
1
Order By: Relevance
“…It has recently been suggested that coordination effects which were held to be a consequence of how actions are represented motorically are in fact due merely to temporal adaptation (e.g. Lelonkiewicz & Gambi, 2016). Could our findings similarly be explained merely by temporal adaptation and so not support the hypothesis that collective goals can be represented motorically?…”
Section: Discussioncontrasting
confidence: 55%
“…It has recently been suggested that coordination effects which were held to be a consequence of how actions are represented motorically are in fact due merely to temporal adaptation (e.g. Lelonkiewicz & Gambi, 2016). Could our findings similarly be explained merely by temporal adaptation and so not support the hypothesis that collective goals can be represented motorically?…”
Section: Discussioncontrasting
confidence: 55%
“…In all cases, compatible action-effect relations help the agent to retrieve the intended motor patterns, whereas incompatible actioneffect relations counteract efficient retrieval. The present findings therefore suggest that A-E compatibility affects action planning in social settings even when controlling for confounding influences of A-E delay (Lelonkiewicz & Gambi, 2016). Experiment 2 went one step further and p i t t e d b o t h , A -E c o m p a t i b i l i t y ( i m i t a t i o n v s .…”
Section: Discussionsupporting
confidence: 47%
“…This possibility remains to be addressed by further empirical work. Alternatively, however, this observation may also be taken to suggest a negligible role of A-E contiguity for the representation of other agents' behavior as long as the delay does not exceed a certain threshold (Lelonkiewicz & Gambi, 2016) and/or the task does not require precise temporal coordination between agents (e.g., Kourtis, Sebanz, & Knoblich, 2010). This speculation receives support from the relatively low accuracies of the detection task in Experiment 2 (pending around 72% on average) and appears to have high face validity because certain delays are a necessary feature of social interaction (because other agents will always require some time to process our actions and respond correspondingly).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations